Contagiousness in treated HIV-1 infection. Issue 1 (8th January 2021) - Eriksen, Jaran; Albert, Jan; Axelsson, Maria; Berglund, Torsten; Brännström, Johanna; Gaines, Hans; Gisslén, Magnus; Gröön, Peter; Hagstam, Per; Navér, Lars; Pettersson, Karin; Stenkvist, Jenny; et al.
Abstract: Background: Effective antiretroviral treatment of HIV-1, defined as continuously undetectable virus in blood, has substantial effects on the infectiousness and spread of HIV. Aim: This paper outlines the assessment of the Swedish Reference Group for Antiviral Therapy (RAV) and Public Health Agency of Sweden regarding contagiousness of HIV-infected persons on antiretroviral therapy (ART). Results and Conclusion: The expert group concludes that there is no risk of transmission of HIV during vaginal or anal intercourse if the HIV-infected person fulfils the criteria for effective ART. Summary: The effective antiretroviral therapy (ART) for HIV-1 infection has dramatically reduced the morbidity and mortality among people who live with HIV. ART also has a noticeable effect on the infectiousness and on the spread of the disease in society. Knowledge about this has grown gradually. For ART to be regarded effective, the level of the HIV RNA in the plasma should be repeatedly and continuously undetectable and the patient should be assessed as continually having high adherence to treatment. Based on available knowledge the Swedish Reference Group for Antiviral Therapy (RAV) and the Public Health Agency of Sweden make the following assessment: There is no risk of HIV transmission during vaginal or anal intercourse if the HIV positive person fulfils the criteria for effective treatment. This includes intercourse where a condom is not used. However, there are a number of other reasons for recommending the use of condoms, primarily to protect against the transmission of other STIs (sexually transmitted infections) and hepatitis, as well as unwanted pregnancy. The occurrence of other STIs does not affect the risk of HIV transmission in persons on effective ART. It is plausible that the risk for transmission of HIV infection between people who inject drugs and share injection equipment is reduced if the individual with HIV is on effective ART, but there are no studies that directly show this. The risk of transmission from mother to child during pregnancy, labour and delivery is very low if the mother's treatment is initiated well before delivery and if the treatment aim of undetectable virus levels is attained. This is dependent on healthcare services being aware of the mother's HIV infection at an early stage. In most contacts with health and medical care, including dental care, the risk of transmission is not significant if the patient is on effective treatment, but the risk may remain, although considerably reduced, in more advanced interventions such as surgery. When an incident with risk of transmission occurs, the patient must always inform those potentially exposed about his or her HIV infection.